Flow characteristics of individual lot stormwater detention - Mah, Darrien Yau Seng; Bong, Charles Hin Joo; Ong, Johnny King Ngu (IWA, 2016)
In this paper the flow characteristics of stormwater are analyzed as it travels from a roof gutter down-pipe and the turbulent flow generated on entering an individual lot on-site stormwater detention (OSD) unit beneath a residential carport. Comparison was made between a full-scale model and computational fluid dynamic (CFD) simulations to determine the flow characteristics. These modular tanks with multi-unit chambers can capture the roof run-off from a 15-minute, 10-year return period storm. The results from the physical and CFD models matched well, suggesting that turbulent flow occurs when stormwater is directed to an individual lot stormwater detention tank. However, turbulence in the OSD was concentrated around the inlet, after which the pattern changed from turbulent to laminar flow. This work implies that the use of modular underground storage tanks is practical for managing stormwater from a roof.